THE CONCEPTUAL PAPER OF BUSINESS MODEL INNOVATION ENVIRONMENTAL FACTOR - Siti Som Husin; Anis Amira Ab Rahman; Dzulkifli Mukhtar, (INTERNATIONAL JOURNAL OF MODERN TRENDS IN SOCIAL SCIENCES (IJMTSS), 2024)
This study draws the themes on environmental factors from two prominent authors in the business model innovation field, Allan Afuah and Alexander Osterwalder, with partner Yves Pigneur. This study reveals that both models have the same concept, even though the arrangement of the process is vice versa. This paper aims to reveal the environmental factors that contribute to a business model innovation. Evidence has shown that the entrepreneur and organization lead to creating the environmental factors in achieving a complete ecosystem in business model innovation. A lack of models and theories in business model innovation studies has led to this study to develop a model based on the entrepreneurship field. Therefore, this study reveals the environmental factors that contribute to the emerging business model innovation. The findings from this study results in a combination of these factors which are categorized based on the current situation. This study is expected to give understanding and knowledge to academicians and will be helpful to practitioners to create and apply a real business model innovation in various industries.